Tổng quan một số nghiên cứu quốc tế về sử dụng quản lí chất lượng tổng thể (TQM) trong các trường trung học cơ sở - Nguyễn, Văn Tám (Tạp chí Giáo dục, 2024)
Total Quality Management (TQM) is a management philosophy that focuses on the continuous improvement of product and service quality through the involvement of all members within an organization. Applying TQM in secondary schools can yield various benefits, including enhancing education quality, improving students' learning experiences, and creating a more effective learning environment. This study synthesizes and analyzes findings from 32 international publications on the application of TQM in secondary schools. The research results indicate that, in addition to its benefits, the application of TQM necessitates key strategies such as focusing on soft aspects, leveraging leadership roles, emphasizing student satisfaction, continuous improvement, teacher training and development, and investment in infrastructure, equipment, and technology. To effectively implement TQM, educational managers must commit to adopting TQM as a comprehensive management philosophy in secondary schools. They should cultivate a cultural environment that supports TQM principles and encourages the participation of all stakeholders.